Judicial Review Of Infrigement Of Superman’s Famous Trademarks Rights: A Case Study Of DC Comic Against PT Maxing Makmur - Mahadewi, Kadek Julia; Rama, Bagus Gede Ari; Amalia, Rafika (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
Well-known trademark infringement is a serious problem that threatens intellectual property rights in the era of globalization. Well-known brands, which have wide recognition in the market, are often the target of infringement by irresponsible parties, which can harm brand owners and consumers. Regulation of Brand Regulation in Law Number 20 of 2016 concerning Trademarks and Geographical Indications in Article 21 regulates trademark registration. Several examples of well-known trademark infringement such as the Supermen case between DC Comic and PT Maxing Makmur experienced trademark problems due to duplication in trademark ownership without considering the existence of Article 21 of the MIG Law. Indonesia adopts a trademark registration system with a constitutive system. The occurrence of a trademark violation makes an article entitled "trademark rights violation (case study of the "superman" trademark DC Comics against PT Marxing Fam Makmur)". The problem in this journal is whether the use of the "Superman" brand by PT Marxing Fam Makmur for its wafer products constitutes a violation of the trademark rights owned by DC Comics? What are the legal consequences of the decision Number 29 / Pdt.Sus / Merek / 2019 / PN Niaga Jkt.Pst on the case of PT Marxing Makmur against DC Comics? The purpose of this study is to examine and analyze the brand problems from the case study. This research method is a normative legal research method. The legal research was conducted with a statutory approach, a case approach which was carried out by reviewing cases related to the issues at hand. The results of the study indicate that PT Marxing Fam Makmur violated the superman brand that has been owned by DC Comics since 1934. So that the cancellation of the superman brand in the name of PT Marxing Fam Makmur was granted.